SINKREISME KEBUDAYAAN BANJAR YANG BERAKULTURASI DENGAN BUDAYA ISLAM (Nilai-nilai Budaya Lokal Dalam Masyarakat) - Abdul Wahab Syakhrani; Fatham Mobina, M. Jarkasi, Ahmad Mua'rrif (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Local community culture can support progress in the field of education. The locality of the Banjar community which will be thick with Islamic-based culture becomes a value that can be applied in the field of education which builds the character of the local sons and daughters. Elements of the values of Islamic culture in Banjar can be seen in terms of social morality, mutual cooperation, caring, good hospitality, and others. With the current flow of globalization, locality must be strengthened through educational institutions, and globalization becomes an arena for promoting moral values of national identity.